Contradictions in practising distributed leadership in public primary schools in New South Wales (Australia) and Slovakia. (27th May 2017) - Miškolci, Jozef
ABSTRACT: The concept of distributed leadership has been widely accepted and scrutinised in research and practice since the beginning of the new millennium. Nonetheless, there is a lack of academic research on how school staff members perceive the term and to what extent they are willing to employ it as part of their daily practices. This article aims to explore these understandings and attitudes in two public primary schools – one in New South Wales (Australia) and one in Slovakia – whilst using qualitative research methods based on semi-structured interviews with staff members. The findings of this study reveal that participants often present very contradictory attitudes towards employing distributed leadership in practice. On the one hand, they require maximising the processes of distributed leadership and, on the other hand, they welcome various instances of solo/autocratic leadership practices by the principal. They also often conflated the concepts of distributed leadership and democratic leadership. In addition, the article discusses how wider social and political context may shape these perceptions and attitudes towards distributed leadership.